The Urgency of Maqāshid al-Syarīah in Strengthening Religious Moderation in Aceh - Husamuddin MZ; Harwis Alimuddin (Al-Risalah, 2022)
Understanding religion (fiqh al-din) is more specific than just knowing religion (al-'ilm bi al-din). Understanding religion will not be realized except by knowing the content and secrets of religion. The science that includes understanding the intentions contained in religious texts is in the study of maqāshid. Among the ways to produce a moderate understanding is to combine particular texts (nashus juz'iyyah) with global intentions (maqāshid kulliyyah). Then the principle that is used as the basis for understanding the text is to look at the difference in meaning in worship and muamalah and distinguish between fixed goals (maqāshid) and changing means (wasīlah). As a sharia area, minorities live in peace in Aceh, there is no conflict between Muslims and non-Muslims. However, the problem has occurred in the internal circles of Muslims in the last ten years as a result of the religious understanding of the Acehnese Muslims. Therefore, it is necessary to look at the concept of moderation in Islamic studies and how urgent the maqāshid al-syarīah approach is to strengthening religious moderation in Aceh. This research is field research with qualitative methods, while the data analysis uses descriptive-analytic with the maqāshid al-syarīah approach. The results show that religious moderation in Islamic studies is not a new thing, known as wasathiyah al-Islām. Then there are not a few who think that the internal moderation of Muslims in Aceh has not been going well and there is still a need for further strengthening and socialization related to religious moderation.